DESERV IT: A Method for Devolving Service Tasks in IT Services - Florian Baer; Kurt Sandkuhl; Michael Leyer; Birger Lantow (Business & Information Systems Engineering, 2020)
Nowadays, IT operations devolve many tasks in IT services to internal customers (i.e., IT self-service). The rationale for this service task devolvement is often to reduce the IT personnel's workload. However, prior research has shown that IT operations often fail to achieve this goal. Existing methods for modeling and analyzing services fall short of supporting service providers in identifying and specifying service tasks suitable to be devolved to (internal) customers. This paper presents, therefore, the first method for devolving service tasks in IT services (DESERV IT). DESERV IT is a compound of four method components encompassing a joint meta-model, a visual notation for modeling IT services, and procedural recommendations. The DESERV IT meta-model extends the meta-model of service blueprinting by means of concepts required to analyze service task devolvement. DESERV IT is evaluated in four evaluation episodes. The results of the evaluation episodes show that DESERV IT is perceived as effective, useful, complete, and generalizable by experts in the IT service management and enterprise architecture discipline. This paper contributes to enterprise modeling by demonstrating the feasibility of DESERV IT in an example case and describing DESERV IT's evolution during the evaluation episodes. DESERV IT supports practitioners (e.g., request fulfillment managers) in modeling and analyzing IT services.
Keywords: 000; Enterprise modeling; Service design; IT service management; IT operations; Self-service